2012
DOI: 10.1002/nau.21241
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rectal distension on bladder function in patients with overactive bladder

Abstract: Rectal distention in patients with OAB symptoms significantly lowered bladder sensation volumes (normal desire, strong desire, and maximal capacity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…24 Conversely, adult studies have demonstrated a decrease in bladder volume at which patients reported first sensation, first desire to void, and strong desire to void with RD. 23,25,26 We demonstrated, for the first time, characteristic changes in intra-anal pressure profiles during the micturition cycle. During bladder filling without RD, there was a significant decrease in intra-anal pressures during voiding and at first quartile of total bladder filling volume.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…24 Conversely, adult studies have demonstrated a decrease in bladder volume at which patients reported first sensation, first desire to void, and strong desire to void with RD. 23,25,26 We demonstrated, for the first time, characteristic changes in intra-anal pressure profiles during the micturition cycle. During bladder filling without RD, there was a significant decrease in intra-anal pressures during voiding and at first quartile of total bladder filling volume.…”
Section: Discussionmentioning
confidence: 72%
“…in their pediatric cohort . Conversely, adult studies have demonstrated a decrease in bladder volume at which patients reported first sensation, first desire to void, and strong desire to void with RD …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…If stretch receptors are stimulated by fecal accumulation, diverse patterns of bladder contraction occur and induce bladder instability . Therefore, the mechanism of OAB mainly involves bowel distention, especially distension of the rectum from fecal retention, rather than constipation itself . As such, the investigation of fecal retention using objective and patient‐friendly tools, rather than the diagnosis of constipation, might be important in the management of OAB in children.…”
Section: Introductionmentioning
confidence: 99%